2017
DOI: 10.3847/1538-4357/aa7fee
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Mass Estimator for Dark Matter Subhalo Perturbations in Strong Gravitational Lenses

Abstract: A few dark matter substructures have recently been detected in strong gravitational lenses though their perturbations of highly magnified images. We derive a characteristic scale for lensing perturbations and show that this is significantly larger than the perturber's Einstein radius. We show that the perturber's projected mass enclosed within this radius, scaled by the log-slope of the host galaxy's density profile, can be robustly inferred even if the inferred density profile and tidal radius of the perturbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 64 publications
10
36
0
Order By: Relevance
“…The values obtained are degenerate, as already found in simulations investigated in Minor et al (2017), Sluse et al (2017), and Vegetti & Vogelsberger (2014). The model-independent approach derived in this work explains these degeneracies from a more general viewpoint, especially the fact that the degeneracy between the perturber and the main lens is not only a degeneracy between different classes of lens models, but a modelindependent degeneracy already contained in the general lensing equations.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The values obtained are degenerate, as already found in simulations investigated in Minor et al (2017), Sluse et al (2017), and Vegetti & Vogelsberger (2014). The model-independent approach derived in this work explains these degeneracies from a more general viewpoint, especially the fact that the degeneracy between the perturber and the main lens is not only a degeneracy between different classes of lens models, but a modelindependent degeneracy already contained in the general lensing equations.…”
supporting
confidence: 72%
“…Vegetti & Koopmans 2009;Vegetti & Vogelsberger 2014), and other ansatzes to describe perturbers, (e.g. Minor et al 2017). Thus, coupling the modelindependent equations, Eqs.…”
Section: General Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Despali et al (2018) have shown that assuming a constant mass-concentration relation from Duffy et al (2008) plays only a secondary effect and leads to an error on the inferred mass of 5 per cent for subhaloes with masses of 10 5−6 M and 20 per cent for masses of 10 9 M . These errors are significantly smaller than the de-projection errors on the total mass of pseudo-Jaffe profiles (Minor et al 2017;Despali et al 2018) and it leads to an error on the expected number of substructures of the order of 10 per cent.…”
Section: Small Mass Haloes As Analytical Mass Componentsmentioning
confidence: 91%
“…On these scales, such substructures would be completely dark matter dominated, and contain too few stars to be observed directly. A number of strategies have been proposed to indirectly probe low mass dark matter halos, including analyses of the impact on Lyα forest observations [14][15][16][17][18][19][20] and perturbations of strong gravitational lenses [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%